Using barbell kinematics to provide the coach with the feedback for the snatch - Chiu, H. T.; Kung, C. Y. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to use three dimensional kinematics of the barbell to provide the coach with quick feedback for the snatch technique of an elite Taiwanese female weightlifter. Three high speed cameras were used to simultaneously record the barbell movements with film frequency of 200 Hz. The horizontal dispalcement-velocity relationship of the barbell seemed to have varied in a certain range while lifting a 95kg barbell. Based on these results, it was recommended the lifter attempt 95kg for her first attempt in the competition. In conclusion, the barbell kinematics is a quick and easy approach to provide the coach with feedback for the snatch. The information of trajectory and movement characteristics of the barbell could provide the coach and the lifter to assist in improving the lifter`s snatch technique.